BARRIERS AND FACILITATORS OF THE INCLUSION OF PEOPLE WITH DISABILITIES IN THE ORGANIZATIONAL CULTURE - Soares da Silva, Daniela; Gomes Veltrone, Thais; Segnini Rodrigues, Lilian (Revista Interface Tecnológica, 2025)
The study analyzed the inclusion of people with disabilities in the corporate environment, considering the scenario in which Brazilian legislation established mandatory quotas and accessibility guidelines, but effective integration still depended on organizational culture. The general objective was to investigate the challenges and facilitators that influenced the inclusion process, while the specific objectives sought to identify physical, attitudinal, and cultural barriers, examine the dual role of organizational culture as both an obstacle and an enabler, and evaluate the effectiveness of public and corporate policies. The research adopted a qualitative approach, based on theoretical review and semi-structured interviews with three people with disabilities employed in the formal labor market. The results showed that participants reported predominantly positive experiences, with no explicit prejudice, strong interpersonal support, and adequate physical accessibility, reinforcing the perception of welcoming environments. However, the study identified that inclusion still occurred mainly in administrative sectors, with gaps in structured institutional policies and in the provision of specific training. It was concluded that legislation favored initial insertion, but full inclusion required consolidated and continuous organizational policies, in order to transform isolated experiences into sustainable strategies of diversity and professional development.